In vitro 3D skin model using gelatin methacrylate hydrogel - Kwak, Bong Shin; Choi, Wonho; Jeon, Joong-won; Won, Jong-In; Sung, Gun Yong; Kim, Bumsang; Sung, Jong Hwan (Journal of industrial and engineering chemistry (Seoul, Korea), 2018)
[Display omitted] Interests in in vitro skin models have been growing. Collagen, which is a main scaffold material for in vitro 3D skin models, has weak mechanical properties, often resulting in undesirable contraction. The physiological characteristics of the skin models often depend on the matrix in which cells are cultured. In this study, we developed a 3D skin model using gelatin methacrylate. The mechanical and transport properties were studied, and attachment and growth of fibroblasts and keratinocytes were examined. Fibroblasts preferred softer matrix, whereas HaCaT cells preferred harder matrix of gelatin methacrylate. This study provides information for developing in vitro skin models.